(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2015)
The use of unsealed radiation sources in nuclear medicine can lead to important incorporation of radionuclides, especially for occupationally exposed individuals (OEIs) during production and handling of radiopharmaceuticals. In this study, computer simulation was proposed as an alternative methodology for evaluation of the absorbed dose distribution and for the effective dose value in OEIs. For this purpose, the Exposure Computational Model (ECM) which is named as FSUP (Female Adult Mesh - supine) were used. This ECM is composed of: voxel phantom FASH (Female Adult MeSH) in the supine position, the MC code EGSnrc and an algorythm simulator of general internal source. This algorithm was modified to adapt to specific needs of the positronic emission from FDG-18F. The obtained results are presented as absorbed dose/accumulated activity. To obtain the absorbed dose distribution it was necessary to use accumulative activity data from the in vivo bioassay. The absorbed dose distribution and the value of estimated effective dose in this study did not exceed the limits for occupational exposure. Therefore, the creation of a database with the distribution of accumulated activity is suggested in order to estimate the absorbed dose in radiosensitive organs and the effective dose for OEI in similar environment.